Paramagnetic phases of four-state Potts model on a Cayley tree in the presence of competing interactions - Ganikhodjaev, Nasir; Rahmatullaev, Anasbek (Taylor & Farncis, 2019)
We consider a Potts model on a Cayley tree with competing nearest neighbor J1 and next-nearest-neighbor interactions Jp restricted to spins belonging to the same branch of the tree with four spins and investigate the problem of phase transition for paramagnetic phases of this mode